2015
DOI: 10.1007/s11060-015-1881-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risk of radionecrosis and imaging changes after stereotactic radiosurgery for brain metastases

Abstract: Radionecrosis is a well-characterized effect of stereotactic radiosurgery (SRS) and is occasionally associated with serious neurologic sequelae. Here, we investigated the incidence of and clinical variables associated with the development of radionecrosis and related radiographic changes after SRS for brain metastases in a cohort of patients with long-term follow up. 271 brain metastases treated with single-fraction linear accelerator-based SRS were analyzed. Radionecrosis was diagnosed either pathologically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
142
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 252 publications
(157 citation statements)
references
References 29 publications
7
142
4
4
Order By: Relevance
“…It has been demonstrated that both larger tumor size and prior WBRT are associated with a higher rate of radionecrosis. 38 On the other hand, it has to be noted that the statistical difference for the higher rate of radiation injury in the group treated with radiosurgery alone is weak (P = .04), and the number of patients in the underlying dataset is too low to derive meaningful conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that both larger tumor size and prior WBRT are associated with a higher rate of radionecrosis. 38 On the other hand, it has to be noted that the statistical difference for the higher rate of radiation injury in the group treated with radiosurgery alone is weak (P = .04), and the number of patients in the underlying dataset is too low to derive meaningful conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…This is higher than for the iPlan plans that have been our clinical standard prior to introducing the VMAT technique but since Gamma Knife plans typically use a PTV D max >140% we accepted this higher inhomogeneity to reduce the GI. The risk of radiation necrosis following cranial SRS has been reported in several studies 13, 14, 15, 16, 17, 18. More data are needed to determine if the difference in dose distribution between the planning techniques have potential clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In the first patient, symptoms developed almost 6 months after the administration of SRS. Although uncommon, it is not impossible to have symptomatic regrowth of lesions-unrelated to tumor recurrence-as early as 6 months after treatment, especially in larger lesions (5). However, given the initial size of the metastatic lesion in this patient, the temporal relationship with pembrolizumab administration, and the more typical delayed development of radiographic and clinical changes following SRS, it is thought that immunotherapy likely played an important role in the pathogenesis of this patient's post-SRS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic changes-unrelated to tumor after stereotactic radiosurgery (SRS) for brain metastasis are well documented (1)(2)(3)(4)(5). Classically, these changes manifest clinically months to years after SRS (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation